MAKNA HAUTEAS DAN RELEVANSINYA BAGI IMAN UMAT SUKU NOPALA, MAUBESI –ATAMBUA - Mataufina, Maria Roswita; Un Bria , Florens Maxi; Abatan , Yofince (Pastoralia Jurnal Penelitian Dosen, 2024)
Hauteas are branching wooden sticks that are considered sacred by the indigenous people of Timor. This tradition is still carried out by the Nopala tribe as part of traditional rituals that reflect happiness, enthusiasm and unity as brothers. This research was conducted to preserve cultural beliefs, deepen the Catholic faith, and strengthen feelings of brotherhood within the tribe, which has an impact on cultural respect between tribes. The method used is qualitative with a naturalistic descriptive approach. Data was collected through observation and in-depth interviews. The research results show that Hauteas functions as a symbolic language for the Nopala Tribe to express their faith in Allah (Uis Neno). Hauteas symbolizes holiness, divinity, and the existence of the Triune God. The process of planting Hauteas and the rituals surrounding it convey deep religious and social significance, strengthening the spiritual connection of the people with God and their ancestors. Hauteas' presence is also relevant to the development of the Catholic faith, because it is a bridge of understanding between ancestral traditions and Catholic teachings. This research concludes that Hauteas is a heritage of faith that is not only a religious symbol but also a means of deepening relationships between tribal members and increasing cross-cultural respect. Preserving these traditions is important to ensure that the spiritual and cultural meaning of Hauteas remains alive amidst changing times.